Perancangan Media Interaktif Buku Papan Permainan Adaptasi Cerita Malin Kundang - carmelita, jessie; Danuputra, Bramanta Octa (Universitas Pembangunan Jaya, 2024)
Indonesian folklore is a cultural heritage that contains important moral values for children's development. Board games, as one of the interactive media, combine education and entertainment, helping to convey moral values as well as train children's social and motor skills. The research was conducted by collecting data through interviews and direct observations on the target audience, namely children, which was then followed by using the 5W+1H method. The design of this game book is intended to invite children to experience the adventure of becoming the character Malin Kundang. Through the creation of this game book, it is hoped that it can help children better understand the moral message of the Malin Kundang folklore and appreciate their parents.